High incidence of FLT3 mutations in follicular thyroid cancer: potential therapeutic target in patients with advanced disease stage. (March 2020) - Borowczyk, Martyna; Szczepanek-Parulska, Ewelina; Dębicki, Szymon; Budny, Bartłomiej; Janicka-Jedyńska, Małgorzata; Gil, Lidia; Verburg, Frederik A.; Filipowicz, Dorota; Wrotkowska, Elżbieta; Majchrzycka, Blanka; Marszałek, Andrzej; Ziemnicka, Katarzyna; et al.
Background: Conventional treatments for follicular thyroid cancer (FTC) can be ineffective, leading to poor prognosis. The aim of this study was to identify mutations associated with FTC that would serve as novel molecular markers of the disease and its outcome and could potentially identify new therapeutic targets. Methods: FLT3 mutations were first detected in a 29-year-old White female diagnosed with metastasized, treatment-refractory FTC. Analyses of FLT3 mutational status through next-generation sequencing of formalin-fixed, paraffin-embedded FTC specimens were subsequently performed in 35 randomly selected patients diagnosed with FTC. Results: FLT3 mutations were found in 69% of patients. FLT3 mutation-positive patients were significantly older than those that were FLT3 mutation-negative [median age at diagnosis 54 (36–82) versus 45 (27–58) ( p = 0.023)]. Patients over 60 years were 23 times more likely to be FLT3 mutation-positive ( p = 0.006). However, the number of FLT3 mutations did not correlate with age ( r -Pearson: –0.244, p -value: 0.25). A total of 26 mutations were identified in the FLT3 gene with 2–16 FLT3 mutations in each FLT3 mutation-positive patient (mean: 5.6 mutations/patient). Tyrosine kinase domain (TKD) mutations in the FLT3 gene were detected in 58% of FLT3 mutation-positive patients. All FLT3 mutation-positive patients with a disease stage of pT2N1 or worse harbored at least one mutation in the TKD of FLT3 . Conclusions: There is a wide spectrum and high frequency of FLT3 mutations in FTC. The precise role of FLT3 mutations in the genesis of FTC, as well as its potential role as a therapeutic target, requires further investigation.